Modeling the high‐latitude ground response to the excitation of the ionospheric MHD modes by atmospheric electric discharge. Issue 11 (8th November 2016) - Fedorov, E.; Mazur, N.; Pilipenko, V.; Baddeley, L.
Abstract: The ionospheric Alfvén resonator (IAR) and fast magnetosonic (FMS) waveguide, which can trap the electromagnetic wave energy in the range from fractions of Hz to several Hz, are characteristic features of the upper ionosphere. Their role in the electromagnetic impulsive coupling between atmospheric discharge processes and the ionosphere can be elucidated with a proper model. The presented model is based on numerical solution of coupled wave equations for electromagnetic modes in the ionosphere and atmosphere in a realistic ionosphere modeled with the use of IRI (International Reference Ionosphere) vertical profiles. The geomagnetic field is supposed to be nearly vertical, so the model can be formally applied to high latitudes, though the main features of ground ULF structure will be qualitatively similar at middle latitudes as well. The modeling shows that during the lightning discharge a coupled wave system comprising IAR and MHD waveguide is excited. Using the model, the spatial structure, frequency spectra, and polarization parameters have been calculated at various distances from a vertical dipole. In the lightning proximity (about several hundred kilometer) only the lowest IAR harmonics are revealed in the radial magnetic component spectra. At distances >800 km the multiband spectral structure is formed predominantly by harmonics of FMS waveguide modes. The model predictions do not contradict the results of search coil magnetometer observations on Svalbard; however, the model validation demands more dedicated experimental studies. Key Points: Numerical modeling shows that lightning stroke excites coupled system of IAR and FMS waveguide In lightning proximity (about few hundred kilometers) only lowest IAR harmonics are stimulated At distances larger than 800 km multiband spectral structure is formed by harmonics of FMS waveguide